Cis-to-trans isomerization of azobenzene investigated by using thin films of metal–organic frameworks1. Issue 35 (21st September 2015) - Yu, Xiaojuan; Wang, Zhengbang; Buchholz, Maria; Füllgrabe, Nena; Grosjean, Sylvain; Bebensee, Fabian; Bräse, Stefan; Wöll, Christof; Heinke, Lars
<x xml:space="preserve">Abstract</x> The energetic barrier for the cis-to-trans isomerization of azobenzene was experimentally investigated by using thin films of azobenzene-containing MOFs as well-defined model system.